Pendampingan Pencatatan Informasi Keuangan Menggunakan Aplikasi Akuntansi Berbasis Android (SIAPIK) untuk Meningkatkan Administrasi Keuangan UMKM - Satriawaty Migang; Yanzil Azizil Yudaruddin; Dwi Susilowati; Wiwik Saraswati; Purwo Atmojo; Ziad Nazila Hakil Udhma; Munawaroh Munawaroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
This community service aims to transfer knowledge to the public regarding knowledge and skills for MSME actors in Balikpapan City to compile financial reports for Small, Micro and Medium Enterprises (MSMEs) using the SIAPIK application issued by Bank Indonesia. The first steps of this service activity use tutorial and workshop methods to explain in theory and practice how to prepare financial statements using the SIAPIK application in recording financial transactions in accordance with SAK EMKM. Second, assistance was carried out regarding the recording of financial transactions through the use of the SIAPIK application to MSMEs in Balikpapan City.